Image conversion of σ- and π-components of radiation of relativistic electron and metrological characteristics of the photon flux in the synchrotron radiation outlet - Mazmanishvili, A.S.; Moskalets, N.V.; Shcherbakov, A.A. (Вопросы атомной науки и техники, 2021)
The paper deals with the efficiency of the capture of a photon flux of the synchrotron radiation (SR) σ- and π-components by the optical window in the SR quantum extraction channel of the NESTOR generator. It also analyses the dependence between the capture quality and different radiation wavelengths. Consideration has been given to the beam size effect on the shape and dimensions of the angular distribution of the photon flux. A model has been constructed to describe the optical imaging in the registration plane. Expressions are given for estimating the efficiency of the capture of SR quanta into the optical window of the extraction channel. The factors that exert influence on the efficiency of capturing through the window are analyzed. Examples of numerical calculations are provided for formation of the final SR spectral density of the 225 MeV relativistic electrons at the output of the optical channel. The dimensions of the optical window have been determined, which ensure the reliable registration of the total flux of SR quanta for the chosen spectral range of SR quanta wavelengths. Вивчена ефективність захоплення потоку фотонів σ- і π-компонент синхротронного випромінювання (СВ) оптичним вікном у каналі виведення квантів СВ, і проаналізована залежність якості захоплення для різних до- вжин хвиль випромінювання. Проведено облік розмірів пучка на форму і розміри кутового розподілу потоку фотонів. Побудована модель, що описує формування оптичного зображення в площині реєстрації. Запропоновано вирази, що дозволяють оцінити ефективність захоплення квантів СВ у оптичне вікно каналу виведення. Проаналізовано фактори, що впливають на ефективність захоплення у вікно. Представлені приклади чисельного розрахунку з формування підсумкової спектральної щільності СВ релятивістського електрона з енергією 225 МеВ на виході оптичного каналу. Отримано розміри оптичного люка, величина яких дозволяє гарантовано реєструвати весь потік квантів СВ для обраного спектрального діапазону хвиль квантів СВ. Изучена эффективность захвата потока фотонов σ- и π-компонент синхротронного излучения (СИ) оптическим окном в канале вывода квантов СИ, и проанализирована зависимость качества захвата для различных длин волн излучения. Проведен учет размеров пучка на форму и размеры углового распределения потока фотонов. Построена модель, описывающая формирование оптического изображения в плоскости регистрации. Предложены выражения, позволяющие оценить эффективность захвата квантов СИ в оптическое окно канала вывода. Проанализированы факторы, влияющие на эффективность захвата в окно. Представлены примеры численного расчета по формированию итоговой спектральной плотности СИ релятивистского электрона с энергией 225 МэВ на выходе оптического канала. Получены размеры оптического люка, величина которых позволяет гарантированно регистрировать весь поток квантов СИ для выбранного спектрального диапазона волн квантов СИ.